The emerging role of TPR-domain immunophilins in the mechanism of action of action of steroid receptors - Mazaira, Gisela Ileana (2014)
In the absence of ligand, some members of nuclear receptor family such as corticosteroid receptors are primarily located in the cytoplasm, and they rapidly accumulate in the nucleus upon ligand-binding. Other members of the family such as the estrogen receptor are mostly nuclear. Regardless of their primary location, these oligomeric proteins undergo a dynamic nuclear-cytoplasmic shuttling, and their transport through the cytoplasmic compartment has always been assumed to occur in a stochastic manner by simple diffusion. Although heuristic, this oversimplified model has never been demonstrated. Moreover, it has always been assumed that the first step related to receptor activation is the dissociation of the Hsp90-based heterocomplex, a process referred to as `transformation.' Nonetheless, recent experimental evidence indicates that the chaperone machinery is required for the retrotransport of the receptor throughout the cytoplasm and facilitates its active passage through the nuclear pore. Therefore, transformation is actually a nuclear event. A group of Hsp90-binding cochaperones belonging to the immunophilin family plays a cardinal role not only in the mechanism for receptor movement, but also in nuclear events leading to interactions with nuclear sites of action and the regulation of transcriptional activity. In this article we analyze the importance of molecular chaperones and TPR-domain immunophilins in the molecular mechanism of action of steroid receptors.